Brazilian Version of the Inventory of the Dimensions of Emerging Adulthood: Investigating the Current Transition to Adulthood - Dutra-Thomé,Luciana (2017)
Abstract The goal of the present study was to analyze the factor structure of the Inventory of Dimensions of Emerging Adulthood (IDEA) in Brazil, in order to use the measure in subsequent studies in the country, and to provide data for comparison of the measure factor structure in different countries. The sample included 547 individuals; residents in Porto Alegre (RS), from low and high SESs, ranging in age from 18 to 29 years old. Results pointed out that the inventory presented a different structure when compared with the original measure. For instance, the item "separating from parents" migrated from the dimension Identity Exploration to Self-focused , influenced by Brazilian cultural specificities. The inventory examined IDEA presented a new factor structure, associated with Brazilian context and the structure of the items on the original measure. In conclusion, the measure is a satisfactory tool of investigation of the emerging adulthood phenomenon in Brazil and Latin America.